OPTIMIZATION OF COMPLEX TREATMENT OF ACUTE PURULENT PERIOSTITIS OF THE JAWS THROUGH RATIONAL USE OF NONSTEROIDAL ANTI-INFLAMMATORY DRUGS (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Objective. To develop and substantiate an optimized approach to the treatment of acute purulent periostitis of the jaws through differentiated prescription of nonsteroidal anti-inflammatory drugs (NSAIDs) based on the severity of pain syndrome and indicators of local immune response.
Keywords: Acute purulent periostitis, pain syndrome, NSAIDs, ketorolac, nimesulide, oral fluid, local immunity.